ASPEK-ASPEK SOSIAL CERPEN MAGIBUNG, PARAS PAROS, DAN CERPEN SARWAGITA DALAM KUMPULAN CERPEN SAWELAS SATUA BAWAK BASA BALI - Ni Wayan, Sukarini (Humanis, 2015)
The study examines the literary works that shapped into the modern Balinese narrative text in the form of short stories. The short stories have been consulted and taken from a collection of short stories Sawelas Satua Bawak Basa Bali made by I Nengah Sudipa. This study examines three short stories in the collection of short stories Sawelas Satua Bawak Basa Bali with entitled Magibung, Paras Paros,and Sarwagita. This study uses the theory of structural. The structural theory using a combination of several literary expert opinion including name of Teeuw and Ratna, but the approach sociology of literature using the opinion of Damono, Wellek and Warren. Methods and techniques used in this study was divided into three stages namely, 1) methods and techniques of data provision, 2) methods and techniques of data analysis, 3) methods and techniques of presenting the results of data analysis. To support these methods use some method of recording techniques and translation techniques. This study revealedthe presence of narrative structure which consist of insiden, alur, latar, tokoh dan penokohan, tema and amanat. This study also reveals the social aspects of aspek tradisi, aspek mata pencaharian, aspek aspek estetika, aspek pendidikan, and aspek kebersamaan.
Keywords: short story, structure, social aspects